PUBLIC-PRIVATE PARTNERSHIP IN THE DEVELOPMENT OF MSMES IN MANGGARAI REGENCY - Jerubu, Hilde Septine; Tiwu, Maria Indriyani Hewe; Kiak, Novi Theresia (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This study aims to analyze the partnership between the government and the private sector in the development of Micro, Small, and Medium Enterprises (MSMEs) in Manggarai Regency. The approach used is descriptive qualitative, with data analysis techniques based on the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Informants consist of representatives from local government agencies (BAPPEDA and the Department of Cooperatives, MSMEs, and Trade), financial institutions (Bank BRI), and MSME actors. The results show that the established partnership has helped improve access to capital, business training, and managerial assistance for MSMEs. Supporting factors for the partnership include pro-MSME government policies, active roles from the private sector, and synergy in empowerment programs. However, there are also obstacles such as complex bureaucracy, limited information, and a lack of financial literacy among MSME actors. This study recommends strategies to strengthen cross-sectoral coordination, simplify administrative procedures, and improve the human resource capacity of MSMEs in order to make the partnership more effective and sustainable.